Implementasi Mekanisme Mini Batch Pada Transmisi Data Elektrokardiografi (EKG) dari Internet of Things (IoT) Gateway Berbasis Perangkat Mobile Android ke Broker MQTT - Dwiyan Ramadhan Dharmanzah; Adhitya Bhawiyuga; Dany Primanita Kartikasari (Jurnal Pengembangan Teknologi Informasi dan Ilmu Komputer, 2021)
Acquisition Electrocardiography (ECG) data using Internet of Things (IoT) technology frequently generate a lot of data that need to considered the quality of ECG data. ECG data has a chance to detect a disease like heart disease. Accordingly, ECG data need high rate of quality for not losing any data when send to any networks. Implementation BLE (Bluetooth Low Energy) is using to support acquisition ECG data from heart sensor to smartphone. ECG data that required are convert to mini-batch in pre-processing method. Formatting mini-batch is done by grouping ECG data from 130 data per second up to 650 data per five seconds and convert to JSON array. Mini-batch data are transmitting to MQTT broker using MQTT QoS level 2 protocol. The testing is done by measuring latency and success ratio from each transmitted data using mini-batch and not using mini-batch. The results of measuring latency using mini batch are maximum latency is 1518 ms, minimum latency is 423 ms and average latency start from 531 ms up to 663 ms. In other measuring test without mini batch are maximum latency is 3389 ms, minimum latency is 1330 ms, and average latency is 1938 ms. In other measuring latency, success ratio also measured and acquired rate of success ratio using mini batch and without mini batch are 100% and 4,261%.